This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using (b + 10)(b + 12) = 0, b = -10, or -12. Sum of the roots is 8 and the product is 10 ( i.e. 1, 2, and 5) or 12 (i.e. 1, 3, and 4). In any case 1 being the root, putting x = 1 in the given equation, 1 - 8 + a + b = 0, Hence (a + b ) = 7